Meal of breadfruit tree (Artocarpus altilis) as alternative substitute for corn in broiler chicken diets - Leyva, Coralia; Valdivie, Manuel; Ortiz, A.; Febles, M.; Dieppa, Oraida (Cuban Journal of Agricultural Science, 2010)
A total of 224 broiler chickens of one day of age of the hybrid HE21 was used to evaluate the inclusion of 0, 10, 20, and 30 % of meal of breadfruit tree (Artocarpus altitis) as substitute for corn in? conventional feedstuffs for broiler chickens. An analysis of variance was performed according to simple classification design with four treatments and seven repetitions. With the inclusion of 0, 10, and 20 % of meal of the breadfruit tree, the viability (98.2, 98.2, and 96.4), the liveweight (1801, 1791, and 1784 g/bird), the weight of the carcass (1131, 1116, and 1108 g/bird), and the weight of the breast (306, 299, and 292 g/bird) did not differ between treatments. Nevertheless, the inclusion of 30 % deteriorated the liveweight, the intake, and the conversion. The cost of the feed per ton of carcass was reduced in 56.39 and 138.54 USD, when including the meal of breadfruit tree at concentrations of 10 and 20 %, respectively. It is recommended to include, as maximum limit, 20 % of the meal of the breadfruit tree in broiler chicken diets. Key words: breadfruit tree, broiler chickens